عائلی نظام میں معاشرۃ با لمعروف کا تصوراور اس کا اطلاق اسلامی تناظر میں - Kalsoom Paracha; Munazza Hayyat (Pakistan Journal of Islamic Research)
The conjugal rights of the two partners in a matrimonial pact belong to social and economic limits according to Islamic Shariah. The title of Muāshrat bil Ma’rūf is taken up to perform those rights and social able relations in a well-disciplined manner. Under this principle the couple has the unanimous privileges and rights of living a pleasant social life, having a matrimonial relation, trying to get issue, rearing up their offspring, avoiding ingratitude behaviour and adopting peaceful ways when they get crossed, or being separated from each other. While the husband has the duty sustaining homely discipline and providing harmonious atmosphere, on the contrary the wife has household responsibilities. And she not only has the right of getting the mandatory heritage and dower (Mehr) or giving it to anybody as gift, but also has the legal right to get the livelihoods of life according the need of hour. Today, the conjugal system in Pakistani society is dwindling to destruction due to its digression from the Quranic doctrines of Muāshrat bil Ma’rūf and its clauses as mentioned in Hadith. The obvious results of deviation for the doctrine seem to be the strife of unnecessary superiority and domination between the better halves, carelessness in bringing up the offspring in right direction, and negligence in regard of the elders. The following article narrates the concept of Muāshrat bil Ma’rūf and it present applications in connubial system in the Islamic concept.